Green Extraction of Bioactives from Curcuma longa Using Natural Deep Eutectic Solvents: Unlocking Antioxidative, Antimicrobial, Antidiabetic, and Skin Depigmentation Potentials - Jelena Jovanović; Marko Jović; Jelena Trifković; Katarina Smiljanić; Uroš Gašić; Maja Krstić Ristivojević; Petar Ristivojević (Plants)
This study evaluates the efficiency of 20 Natural Deep Eutectic Solvents (NADES) formulations for extracting curcuminoids and other bioactive compounds from turmeric and emphasize their ability to preserve and enhance antioxidant, antimicrobial, antidiabetic, and skin depigmentation effects. The NADES formulations, prepared using choline chloride (ChCl) combined with sugars, carboxylic acids, glycerol, amino acids, urea, polyols, and betaine, were assessed for their extraction efficiency based on the total phenolic content and curcumin concentration. Fourier transform infrared spectroscopy was employed to characterize the synthesized NADES and confirm their chemical composition. Bioactivity evaluations included antioxidant assays (ABTS and DPPH), antidiabetic tests (α-amylase inhibition), antimicrobial assays, and skin depigmentation (tyrosinase inhibition). The results demonstrated that NADES significantly enhanced the extraction efficiency and bioactive properties of turmeric extracts compared to water as a conventional green solvent. NADES 18 (ChCl/1,2-propanediol/water 1:1:1) and NADES 19 (glycerol/betaine/water 1:1:3) exhibited the highest extraction yields, with curcumin concentrations of 30.73 ± 1.96 mg/g and 31.70 ± 2.02 mg/g, respectively, outperforming water (26.91 ± 1.72 mg/g), while NADES 17 (ChCl/1,2-propanediol/water 0.5:3:0.5:5) and NADES 20 (glycerol/lysine/water 1:1:3) exhibited the most potent antioxidant activity. Furthermore, NADES 14 (ChCl/lactic acid/water 1:2:5) demonstrated the strongest tyrosinase inhibition (98.7%), supporting its potential for skin-brightening applications, including notable α-amylase inhibition exceeding 90%. This study aligns with the principles of green chemistry, as NADES are effective and sustainable solvents for natural product extraction. The presenting benefits of improved extraction efficiency and enhanced bioactivities position NADES as a promising and eco-friendly approach for developing efficient bioactive compound extraction methodologies.